Régimen oral abreviado para la tuberculosis multidrogorresistente. - Jiménez Jiménez, Yessenia Mercedes; Reasco Macas, Melissa Cecilia (My University, 2024)
Tuberculosis (TB) is one of the diseases with a high level of morbidity and mortality after COVID-19, it is a chronic condition caused by Mycobacterium Tuberculosis, multidrug-resistant tuberculosis (MDR-TB) is a challenge when outlining treatment to combat this condition., manifests itself in an insidious manner, exhibiting high clinical severity. For this reason, the focus of this research will be directed towards the analysis of the short oral MDR-TB regimen considering the complexity that this disease implies and the application of new therapeutic strategies. Objective: Analyze the advances in treatment for multidrug-resistant pulmonary tuberculosis through critical reading of articles from high-impact journals to help mitigate morbidity and mortality from this disease. Method: This research is observational, descriptive and retrospective, studies were used in patients with MDR-TB between 14 and 60 years of age. Scientific databases such as PubMed, SciELO, Scopus, Elsevier, Science Direct, Redalyc and EBSCO were used. Specific health descriptors, UNESCO thesauri, and MeSH terms were used for the search. In addition to the use of the Boolean search engines “And”, “Or”, and “Not” and finally the SCIMAGO platform for the selection of articles. Result: Indeed the information obtained through a critical analysis reveals that an oral regimen of BPaL for 6 months is a safe and simple alternative with at least a 93% success rate for patients with MDR-TB with or without resistance to fluoroquinolones, in addition to its cost-benefit characteristic that allows greater accessibility and adherence to treatment. Conclusions: The study highlights advances in MDR-TB treatment and new short-term therapeutic options that have shown promising results for patients. The 26-week treatment regimens with BPaL and BPaLM are highly effective, although the former is more tolerated in fluoroquinolone-resistant patients. These schemes are also cost-effective and viable, contributing to improving access to treatment
La tuberculosis (TB) es una de las enfermedades con un alto nivel de morbimortalidad después del COVID-19, es una afección crónica producida por Mycobacterium Tuberculosis, la tuberculosis multidrogorresistente (TB-MDR) es un desafío esquematizar el tratamiento para combatir esta afección, se manifiesta de manera insidiosa, exhibiendo una elevada gravedad clínica. Por este motivo, el enfoque de la presente investigación se dirigirá hacia el análisis del régimen oral corto de TB-MDR considerando la complejidad que esta enfermedad implica y la aplicación de nuevas estrategias terapéuticas. Objetivo: Analizar los avances del tratamiento para tuberculosis pulmonar multidrogorresistente mediante la lectura crítica de artículos de revistas de alto impacto para contribuir a mitigar la morbimortalidad por esta enfermedad. Método: La presente investigación es de carácter observacional, descriptivo y retrospectivo, se emplearon estudios en pacientes con TB-MDR entre los 14 y 60 años. Se utilizaron bases de datos científicas como, PubMed, SciELO, Scopus, Elsevier, Science Direct, Redalyc y EBSCO. Para la búsqueda se empleó descriptores de salud específicos, tesauros de la UNESCO, términos MeSH. Además del empleo de los buscadores booleanos “And”, “Or”, y “Not” y finalmente para la selección de artículos la plataforma SCIMAGO. Resultado: En efecto de la información obtenida por medio de un análisis crítico revela que un régimen oral de BPaL durante 6 meses es una alternativa segura y sencilla con al menos una taza del 93% de éxito para los pacientes con TB-MDR con o sin resistencia a las fluoroquinolonas, además de su característica costo-beneficio que permite una mayor accesibilidad y adherencia al tratamiento. Conclusiones: El estudio destaca los avances en el tratamiento de TB-MDR y las nuevas opciones terapéuticas de corto plazo que han mostrado resultados prometedores para los pacientes. Los regímenes de tratamiento de 26 semanas con BPaL y BPaLM son altamente efectivos, aunque el primero es más tolerado en pacientes resistentes a fluoroquinolonas. Estos esquemas son también costo-eficaces y viables, contribuyendo a mejorar el acceso al tratamiento.
Keywords: TUBERCULOSIS MULTIDROGORRESISTENTE; TRATAMIENTO ANTITUBERCULOSO; BEDAQUILINA; PRETONAMIDA